Adolescent Presents With Altered Mental Status and Elevated Anion Gap After Suicide Attempt by Ethylene Glycol Ingestion. Issue 10 (October 2016) - Schoen, Jessica C.; Cain, Meghan R.; Robinson, Jeffrey A.; Schiltz, Brenda M.; Mannenbach, Mark S.
Abstract : Abstract: We report the case of a 16-year-old healthy adolescent male who presented to the local emergency department with altered mental status. En route to a tertiary care facility, he began to decompensate and was found to be markedly acidotic. Further investigation revealed an elevated anion gap, and physical examination showed only abdominal pain and decreased level of consciousness. A broad differential diagnosis was considered at the time of the patient's presentation at the tertiary care center including ingestion of a volatile alcohol, sepsis, and an abdominal catastrophe. Although fomepizole and emergent dialysis were being initiated, laboratory tests confirmed ethylene glycol poisoning. This case demonstrates the importance of early recognition of potential ingestions in patients with altered mental status and supportive laboratory findings.